1993
DOI: 10.1038/366166a0
|View full text |Cite
|
Sign up to set email alerts
|

Complementation by the protein tyrosine kinase JAK2 of a mutant cell line defective in the interferon-& gamma; signal transduction pathway

Abstract: Interferons (IFNs) alpha/beta (type I) and gamma (type II) bind to distinct cell surface receptors, inducing transcription of overlapping sets of genes by intracellular pathways that have recently attracted much attention. Previous studies using cell lines selected for their inability to respond to IFN-alpha (ref. 4) have shown that the protein kinase Tyk2 plays a central role in the IFN alpha/beta response. Here we report the isolation of the cell line gamma 1A, selected for its inability to express IFN-gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
263
0
4

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(276 citation statements)
references
References 25 publications
9
263
0
4
Order By: Relevance
“…Another set of mutants, the g mutants, failed to respond to IFN-g, but retained their IFNa/b responsiveness. Ectopic expression of JAK2, but not TYK-2 or JAK-1 in these cells resulted in the restoration of cellular response to IFN-g (Watling et al, 1993). Studies with U4 mutant cell line , which was unable to respond to either IFN-a/b or g revealed that it had a truncated JAK1 transcript and introduction of JAK1 expression constructs into these cells resulted in restoration of the IFN-a/b and g response.…”
Section: Stat Signaling Pathwaysmentioning
confidence: 92%
See 1 more Smart Citation
“…Another set of mutants, the g mutants, failed to respond to IFN-g, but retained their IFNa/b responsiveness. Ectopic expression of JAK2, but not TYK-2 or JAK-1 in these cells resulted in the restoration of cellular response to IFN-g (Watling et al, 1993). Studies with U4 mutant cell line , which was unable to respond to either IFN-a/b or g revealed that it had a truncated JAK1 transcript and introduction of JAK1 expression constructs into these cells resulted in restoration of the IFN-a/b and g response.…”
Section: Stat Signaling Pathwaysmentioning
confidence: 92%
“…Studies with interferon (IFN) receptor signaling have revealed that JAK family kinases are involved in IFN-speci®c gene expression in cooperation with STATs (Darnell et al, 1994;Schindler and Darnell, 1995). Studies with mutant cell lines, which were unable to respond to interferons, were used to dissect the interferon signaling pathways Watling et al, 1993). In one set of studies, a mutant cell line designated as U1 was used which failed to respond to IFN-a or IFN-b but remained responsive to IFNg.…”
Section: Stat Signaling Pathwaysmentioning
confidence: 99%
“…Although hemopoietic cytokine receptors appear to require JAK tyrosine kinase activity for STAT DNAbinding activity Watling et al, 1993) recent data has suggested that for growth-factor receptors this is not the case (Leamann et al, 1996;Vignais et al, 1996). These studies have demonstrated that either the intrinsic kinase activity of these receptors or an unde®ned downstream tyrosine kinase is involved.…”
Section: Insulin-induced Dna-binding Activity Requires Tyrosine But Nmentioning
confidence: 99%
“…This tyrosine phosphorylation of STATs provides both a nuclear localization signal and also allows dimerization critical for DNA-binding (Shuai et al, 1993(Shuai et al, , 1994. For receptors containing no intrinsic tyrosine kinase activity, the Janus kinase family (JAKs) appear to be responsible for the activating STAT-phosphorylation Silvennoinen et al, 1993;Watling et al, 1993;Schindler and Darnell, 1995). However, for growthfactor receptors, which do contain an intrinsic kinase activity, such as the EGF and PDGF receptors, the STAT-phosphorylating activity has not been unequivocally determined (Shuai et al, 1993;Zhong et al, 1994;Co er and Kruijer, 1995;Leaman et al, 1996;Vignais et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The tyk/jak family is made up of a unique set of tyrosine kinases (distinct from src family tyrosine kinases) that are between 120 kd and 140 kd in size, have no SH2 or SH3 domains, and have 2 kinase domains, of which only one appears to be functional. That other tyrosine kinases from the tyk2/Jak family are also involved in IFN signaling was shown when the Kerr-Stark group developed other mutants for IFNa and IFNy signaling: for IFNa, Jakl and tyk2 are required; for IFNy, it is Jakl and Jak2 (46,47). In support of the complementation studies described above, biochemical investigations from several groups of investigators have confirmed the role of tyk2 and Jakl in IFNa signaling, and of Jakl and Jak2 in IFNy signaling (48)(49)(50).…”
Section: Ifn Activation Of the Stat Proteinsmentioning
confidence: 99%